Effect of Basis Sets on the Selection of the Level of Theory Toward the Development of Quantum-Based Force Field Equation for Ionic Liquids - A. N. Soriano; B. T. Doma, Jr. (ASEAN Journal of Chemical Engineering, 2005)
The chemical industry is under considerable pressure to replace many of the volatile organic compounds. Volatile organic compounds are a major contributor to air pollution, but out of necessity, they are still frequently used in many chemical and industrial processes. A new class of solvents, referred to as ionic liquids, may offer at least a partial solution to the pollution problem caused by volatile organic compounds. Ionic liquids are generally considered "green" solvents because of their environment-friendly properties. However, the main problem that hinders the chemical industry from using ionic liquids is that, compared to conventional organic solvents, relatively little is known about their thermodynamic and transport properties. Since there are large possible combinations of ionic liquids, it would be very expensive if the study were conducted in the laboratory. The more appropriate approach in studying the properties of ionic liquids is to engage in a computational method, which uses a computer software that evaluates ionic liquids' thermophysical quantities via quantum mechanical and molecular mechanical simulations. In this study, a computer simulation, with the aid of SPARTAN '02 software, is used to study the effect of basis sets on the selection of the appropriate level of theory, which would be employed later in developing a quantum-based force field equation for predicting the properties of ionic liquids. Using the Hartree-Fock self-consistent filled (HF-SCF) molecular orbital model with different basis sets, a single point energy calculations were carried out for the chosen ionic liquid. With the exception of the minimal basis set, the SCF total energies for the other basis sets agree with each other in terms of magnitude. The SCF total energy is not affected as the basis set varies from minimal to split valence and as it polarizes. The most appropriate basis set was found to be 6-31G*. Keywords: Basis sets, Hartree-Fock, ionic liquids, force field equation, level of theory, and SPARTAN '02.